METAMORFOSISI SANTRI DIGITAL: TRANSFORMASI PEMBELAJARAN KITAB KUNING MELALUI PODCAST INTERAKTIF PESANTREN MODERN - Kurniawan, M.Agus; Puspitasari, Ema (Indonesian Society and Religion Research, 2025)
In the digital era marked by rapid advancements in information and communication technology, the transformation of traditional Islamic education, particularly the learning of classical Islamic texts (kitab kuning) in pesantren, has become essential for maintaining relevance and effectiveness. This study examines how pesantren are integrating digital technology into their teaching of kitab kuning and the subsequent impact on the quality of Islamic education. Through an in-depth analysis of various implementations of digital technology in prominent pesantren, this research highlights several innovative learning methods developed, including the use of digital platforms, interactive podcasts, and technology-based evaluation systems. The findings indicate that digital transformation not only enhances accessibility and efficacy of learning but also reinforces the position of pesantren as adaptive Islamic educational institutions in a changing world. In conclusion, the integration of digital technology in the study of kitab kuning represents the ability of pesantren to preserve tradition while embracing modern innovation, thus creating a more comprehensive and sustainable model of Islamic education in the digital age.